Carcinops pumilio (Erichson) (Coleoptera: Histeridae) as a predator of house flies in poultry manure - Achiano, K. A. (Kwaku Akoming) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2004.